2015
DOI: 10.1158/1078-0432.ccr-14-2142
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Induced Tumor Necrosis Factor–Producing T Cells Synergize with Cisplatin to Promote Tumor Cell Death

Abstract: Purpose: Cancer immunotherapy, such as vaccination, is an increasingly successful treatment modality, but its interaction with chemotherapy remains largely undefined. Therefore, we explored the mechanism of synergy between vaccination with synthetic long peptides (SLP) of human papillomavirus type 16 (HPV16) and cisplatin in a preclinical tumor model for HPV16.Experimental Design: SLP vaccination in this preclinical tumor model allowed the elucidation of novel mechanisms of synergy between chemo-and immunother… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 45 publications
0
64
1
Order By: Relevance
“…45 In this study, clinical response and survival were found to be correlated with induction of WT1-reactive CD8 For personal use only. on May 11, 2018.…”
Section: Discussionmentioning
confidence: 55%
“…45 In this study, clinical response and survival were found to be correlated with induction of WT1-reactive CD8 For personal use only. on May 11, 2018.…”
Section: Discussionmentioning
confidence: 55%
“…Ten days after the start of therapy, the tumor-specific CD8 T-cell response is sufficiently elevated to mediate a robust regression of tumors with sizes up to 600 mm 3 . However, the independently derived HPV16 tumor line C3 responds to prophylactic but not to therapeutic vaccination with the same SLP vaccine modality (5,19). To better understand these differences, we analyzed tumor-infiltrating leukocytes 10 days after peptide vaccination, when TC-1 tumors just start to regress but C3 tumors continue to grow.…”
Section: Infiltration Of Tumor-specific Cd8 T Cells Coincides With Inmentioning
confidence: 99%
“…The two HPV oncogenes E6 and E7 are critical for maintenance of cellular transformation; they are constitutively expressed by HPV-associated tumors and are therefore ideal targets for therapeutic vaccination (3). We have shown that overlapping synthetic long overlapping peptides (SLP) comprising these proteins are capable of inducing potent T-cell responses in mice and humans (4)(5)(6)(7). In patients with premalignant lesions, vaccine-induced T-cell responses correlate with complete clinical responses.…”
Section: Introductionmentioning
confidence: 99%
“…165). An additional mechanism of improved tumor eradication by chemoimmunotherapy is cisplatin-mediated lowering of the tumor apoptosis threshold by TNF-α released from vaccine-induced intratumoral T cells (166). Another obvious choice for combination treatment is the addition of checkpoint-blocking agents to therapeutic vaccination, which has yielded promising results in preclinical models ( Figure 3B and refs.…”
Section: Guidelines For the Development Of Successful Therapeutic Canmentioning
confidence: 99%